Convective heat and mass transfer - Ghiaasiaan, Seyed Mostafa, 1953- (Cambridge University Press, 2011)
"This book was developed during Professor Ghiaasiaan's ten years of teaching a graduate-level course on convection heat and mass transfer and is further enhanced by his twenty years of teaching experience. The book is ideal for a graduate course dealing with the theory and practice of convection heat and mass transfer. The book treats well-established theory and practice but is also enriched by its coverage of modern areas such as flow in microchannels and computational fluid dynamics-based design and analysis methods. The book is primarily concerned with convection heat transfer. Essentials of mass transfer are also covered. The mass transfer material and problems are presented such that they can be easily skipped. The book is richly enhanced by examples and end-of-chapter exercises. Solutions are available for qualified instructors. The book includes 18 appendices providing compilations of most essential property and mathematical information for analysis of convective heat and mass transfer processes"-- Provided by publisher.
Keywords: Heat -- Convection.; elektronické knihy; electronic books